2017
DOI: 10.1186/s12871-017-0384-5
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life perceptions among physicians in intensive care units managed by anesthesiologists in Germany: a survey about structure, current implementation and deficits

Abstract: BackgroundStructural aspects and current practice about end-of-life (EOL) decisions in German intensive care units (ICUs) managed by anesthesiologists are unknown. A survey among intensive care anesthesiologists has been conducted to explore current practice, barriers and opinions on EOL decisions in ICU.MethodsIn November 2015, all members of the German Society of Anesthesiology and Intensive Care Medicine (DGAI) and the Association of German Anesthesiologists (BDA) were asked to participate in an online surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
(30 reference statements)
2
12
1
Order By: Relevance
“…In the present study, decision-making to integrate a palliative approach in intensive care is influenced by healthcare professionals’ knowledge and attitudes about the transition from curative-focused to palliative-focused goals of care, which highlights the importance of focusing on healthcare professionals’ goal-setting attitudes and abilities in the integration of a palliative approach [ 46 ]. Unsurprisingly, having a clear goal of care on admission to the ICU seems to support professionals in the palliative decision-making process [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, decision-making to integrate a palliative approach in intensive care is influenced by healthcare professionals’ knowledge and attitudes about the transition from curative-focused to palliative-focused goals of care, which highlights the importance of focusing on healthcare professionals’ goal-setting attitudes and abilities in the integration of a palliative approach [ 46 ]. Unsurprisingly, having a clear goal of care on admission to the ICU seems to support professionals in the palliative decision-making process [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the barriers hindering an adequate EOLC provision are related to the medical professionals themselves, mostly due to their lack of knowledge or legal/ethical concerns [4]. A survey conducted among 541 German intensive care anaesthesiologists identified lack of training as the main barrier to implementing EOLC in Germany [13]. This concern has been raised recently by other authors reporting that not even 50% of a large cohort of Italian and American critical care professionals surveyed confirmed that they had training in EOLC [8,14].…”
Section: Discussionmentioning
confidence: 99%
“…These questions were modified from previous studies [ 29 , 30 ]. The practice of goals-of-care discussions using a four-point Likert scale (1: always, 2: usually, 3: not much, 4: not at all) on the following six items: (1) discussions are held with the family, (2) a nurse is involved; (3) using a room that ensures privacy; (4) the understanding of the patient’s family is confirmed; (5) details of the discussion are documented in the medical record; and (6) a summary of the discussion is provided to the family.…”
Section: Methodsmentioning
confidence: 99%